The challenges of implementing urban transport policy in the Klang Valley, Malaysia - Raja Ariffin, Raja Noriza; Zahari, Rustam Khairi (Elsevier, 2013)
This paper analyses the implementation of policy and administration of urban transportation system in the Klang Valley, Malaysia. The Klang Valley was chosen as the study area due to its phenomenal growth in the last two decades that affected the administration of its urban transportation system. Interviews were utilized as the main research instrument. The examination of the practices, attitudes and beliefs of those working in the transport related field have shed some light on the relationship between agencies and the impact that these have upon transportation system in the Klang Valley. Other than interviews, these examinations involved investigating the history and current status of the policy development, implementation as well as administration, which were obtained through an examination of government documentation, archival records, and observation. It was found that the lack of synergy in the implementation and administration of the system has taken its toll on the efficiency and effectiveness of the system.